Human Developmental Toxicants: Aspects of Toxicology and Chemistry - Schardein, James (CRC Press, 2009)
Presenting the first database of its kind, this unique reference illustrates the relationships between the chemistry and developmental toxicity of a number of important pharmaceuticals and industrial toxicants. Human Developmental Toxicants contains up-to-date and concise information on the chemical structures, properties, and biological activities for 50 known agents that adversely affect prenatal and postnatal human development in terms of growth, viability, structure, and function.